Case Report: Complete pathologic response to neoadjuvant selpercatinib in a patient with resectable early-stage RET fusion-positive non-small cell lung cancer - Goldman, Jonathan W.; Sholl, Lynette M.; Dacic, Sanja; Fishbein, Michael C.; Murciano-Goroff, Yonina R.; Rajaram, Ravi; Szymczak, Sylwia; Szpurka, Anna M.; Chao, Bo H.; Drilon, Alexander (Frontiers in Oncology, 2023)
The LIBRETTO-001 trial demonstrated the activity of the selective RET (rearranged during transfection) inhibitor selpercatinib in advanced RET fusion-positive non-small cell lung cancer (NSCLC) and resulted in the drug’s approval for this indication. A cohort that included neoadjuvant and adjuvant selpercatinib was opened on LIBRETTO-001 for early-stage RET fusion-positive NSCLC with the primary endpoint of major pathologic response. A patient with a stage IB (cT2aN0M0) KIF5B-RET fusion-positive NSCLC received 8 weeks of neoadjuvant selpercatinib at 160 mg twice daily followed by surgery. While moderate regression in the primary tumor (stable disease, RECIST guidelines version 1.1) was observed radiologically, assessment via an Independent Pathologic Review Committee revealed a pathologic complete response (0% viable tumor). This consensus assessment by three independent pathologists was aided by RET fluorescence in-situ hybridization testing of a reactive pneumocyte proliferation showing no rearrangement. Neoadjuvant selpercatinib was well-tolerated with only low-grade treatment-emergent adverse events. The activity of prospective preoperative selpercatinib in this case establishes proof of concept of the potential utility of RET inhibitor therapy in early-stage RET fusion-positive NSCLC.